Maqasid Al-Shariah and Child Protection: A Holistic Approach to Preventing Early Marriage - Azam Sukri; Aris Fauzan (Universitas Islam Negeri Madura, 2025)
This research presents a novel and holistic approach to addressing child marriage by explicitly integrating the Maqasid Al-Shariah framework—comprising the protection of religion, life, intellect, lineage, and property—as its primary analytical lens. Unlike previous studies that often treat the social, health, legal, or religious aspects of child marriage in isolation, this study unifies these dimensions within an Islamic ethical paradigm. This study employs a qualitative literature review method, systematically collecting, evaluating, and synthesizing secondary data from Islamic jurisprudence, legal frameworks, and child welfare reports to analyze child protection and adolescent well-being through the lens of Maqasid Al-Shariah. The findings of this research reveal that integrating the Maqasid Al-Shariah framework into strategies for addressing child marriage significantly enhances both the religious legitimacy and community acceptance of child protection efforts. Child marriage is a complex issue that fundamentally contradicts the five core objectives of Maqasid Al-Shariah—protection of life, intellect, lineage, property, and religion—making its elimination a religious as well as social imperative. This research highlights that child marriage endangers children's physical and mental health, disrupts education, and undermines family and community wellbeing. Addressing the issue requires more than legal reforms; it demands collaboration among policymakers, religious scholars, and community leaders to correct misinterpretations of Islamic teachings and shift cultural norms